Analisis Perhitungan HPP dengan Metode Full Costing sebagai Dasar Penerapan Harga Jual Pada UMKM Pecel Lele 78 Pluit Jakarta Utara : Analysis of HPP Calculation with Full Costing Method as the Basis for the Implementation of Selling Prices in MSMEs Pecel Lele 78 Pluit North Jakarta - Citra Puspita; Puji Lestari; Safira Aulya; Jihan irani; Nazwa Maulida (PT Cakrawarti Empat Proksi, 2026)
This study was motivated by the fact that many MSME operators, particularly in the culinary sector, set their selling prices without conducting a comprehensive calculation of production costs. This can lead to inaccuracies in pricing and affect business profits. The objective of this study is to analyze the calculation of the cost of goods sold using the Full Costing method and its implications for pricing at the Pecel Lele 78 MSME in Pluit, North Jakarta. This study employs a descriptive qualitative method using both primary and secondary data sources. Data were collected through interviews, observations, and documentation, then analyzed by comparing the cost of goods sold calculations performed by business owners with those calculated using the Full Costing method. The results of the study indicate a difference of Rp 2,000 between the selling price calculated using the Full Costing method and the selling price determined by UMKM Pecel Lele 78. Furthermore, the selling price calculated using the Full Costing method is higher than the price currently applied by the business. These findings suggest that the Full Costing method can serve as a reliable basis for determining selling prices, as it enables businesses to maximize profits while maintaining product competitiveness in the market.